Pengaruh Dosis Dan Interval Pemberian Pupuk Biokomplex Terhadap Pertumbuhan Dan Hasil Tanaman Selada Keriting (Lactuca Sativa L.) - bagus rahmawan (AGRONISMA, 2021)
Curly lettuce (Lactuca sativa L) is a horticultural plant that is in great demand by the public today and contains many nutrients and vitamins, including: Calcium, Phosphorus, Iron, Vitamins A, B and C. The negative effect of the green revolution lasting more than 30 years, one of the factors is the field of fertilization resulting in reduced ecosystems in the soil. Biocomplex biofertilizer is one alternative because it can help improve the ecosystem in the soil. This study aimed to study the effect of dosage and interval of application of biocomplex fertilizer on the growth and yield of curly lettuce. The design used was a factorial randomized block design consisting of 2 factors. The first factor consists of a dose of biocomplex fertilizer (100 ml/polybag and 200 ml/polybag). The second factor consisted of the interval of application of biocomplex fertilizers (3 days before planting, 3 days before and 1 time after planting, 3 days before and 2 times after planting, 3 days before and 3 times after planting) and control. The results showed that there was a significant interaction on the total fresh weight parameter of plants (D2T4 = 88.25 grams) which showed better results than other treatments and controls. Treatment D2 (dose of 200 ml/polybag) gave optimal results at the economic weight of curly lettuce plants reaching 53.79 grams. The T4 treatment (4 times interval) of biocomplex fertilizer gave optimal results on the dry weight of curly lettuce plants reaching 6.40 grams